Ambidextrous leadership and innovation: a process perspective and an experimental approach - Yiheng Xi; Li Zhou; Haiyan Wang (Humanities & Social Sciences Communications)
Abstract Ambidextrous leadership is a context-based combination of opening and closing leadership behaviors, and is thought to enhance both leader and employee behaviors in complex innovation processes. Existing studies on ambidextrous leadership and innovation tend to treat innovation as a unitary construct, without specifically distinguishing between different innovation processes or stages, thus failing to test the applicability of ambidextrous leadership based on the heterogeneity of the innovation process. Besides, previous studies have predominantly used survey- or diary-based research designs, thus preventing causal inferences. Our study used two randomized controlled experiments (N = 250) on two simulated innovation tasks by manipulating four leadership styles (ambidextrous, opening, closing, and transformational leadership) to validate the causal effect of ambidextrous leadership on two different innovation processes (idea generation and idea implementation). The findings broadly support the adaptive value of ambidextrous leadership in both idea generation and implementation, suggesting that both opening and closing leadership behaviors may be needed in idea generation and implementation when the situation requires (although the opening and ambidextrous leadership interventions did not differ in idea generation). It indicates that leaders of organizational innovation teams in real-world scenarios should adaptively employ a combination of opening and closing leadership behaviors to optimize team innovation performance, contingent on the particular stage and situational demands of the innovation task. Subsequent research could employ a more ecologically valid dynamic observation methodology and investigate the applicability and mechanism of ambidextrous leadership under diverse antecedent conditions.